Typical meteorological year based on the precipitation of Nanegalito and Pacto-Ecuador - Rodríguez, Francisco; Castro, Andrea; Marín, Freddy; Roldán, Gloria; Viteri Moya, Fausto (Enfoque UTE, 2019)
The typical meteorological year (TMY) based on daily rainfall data was calculated in the parish of Nanegalito; 12 years were considered, from 2004 to 2015, including both years. For the establishment of the TMY, the Finkelstein-Schafer (FS) statistical equation was chosen, together with the calculation of the cumulative distribution function for each month of each year considered. The weighted sum, calculated from the FS values, was used to finally choose the months that best represent the climatic characteristics of the period analyzed by applying the root mean square deviation (RMSD). Once these values were obtained, the TMY of Nanegalito was estimated based on the precipitation. The determination of Nanegalito TMY may be useful for the management of several processes, in this and other surrounding parishes, as an example, Pacto, such as irrigation planning in crops, analysis in drought risk scenarios, and if other variables are analyzed in the future, they could serve as tools for the study of possible renewable energies.